An improved model-based technique for generating test scenarios from UML class diagrams - Oluwagbemi, O. (IGI Global, 2014)
The foundation of any software testing process is test scenario generation. This is because it forecasts the expected output of a system under development by extracting the artifacts expressed in any of the Unified Modeling Language (UML) diagrams, which are eventually used as the basis for software testing. Class diagrams are UML structural diagrams that describe a system by displaying its classes, attributes, and the relationships between them. Existing class diagram-based test scenario generation techniques only extract data variables and functions, which leads to incomprehensible or vague test scenarios. Consequently, this chapter aims to develop an improved technique that automatically generates test scenarios by reading, extracting, and interpreting the sets of objects that share attributes, operations, relationships, and semantics in a class diagram. From the performance evaluation, the proposed modelbased technique is efficiently able to read, interpret, and generate scenarios from all the descriptive links of a class diagram.